The High‐Latitude Dawn‐Dusk Asymmetry of Ionospheric Plasma Distribution in the Northern Hemisphere. Issue 7 (11th July 2022) - Wang, Jianping; Zhang, Beichen; Huang, Chunming; Liu, Ruiyuan; Yang, Shenggao; Huang, Yanshi; Hu, Hongqiao; Yang, Huigen
Abstract: The high‐latitude dawn‐dusk asymmetrical distribution of the Mean Total Electron Content (MTEC) in the northern hemisphere was statistically investigated using Global Navigation Satellite System (GNSS) vertical TEC data in 2014. In the geomagnetic latitude (MLAT)/geomagnetic local time (MLT) coordinate system, the local time of 0 hr ≤ MLT < 12 hr is defined as the dawn, and 12 hr ≤ MLT < 24 hr is defined as the dusk at MLAT is greater than 70°. The sunlit high‐density plasma at lower latitudes in the postnoon sector is the primary source of the asymmetrical MTEC distribution that the duskside MTEC is larger than the dawnside. Except for summer, the diurnal variations of the dusk‐dawn difference (DMTEC) and dusk‐dawn ratio (DDR) have two peaks and two valleys. The DMTEC and DDR also have significant seasonal variation, which is the greatest in spring (2.9TECu and 22.2%) and the smallest in summer (1.0TECu and 9.2%). The DMTEC and DDR depend significantly on the Kp index and the direction of interplanetary magnetic field (IMF). Except for the DMTEC in spring, the DMTEC and DDR are larger during disturbed times than during quiet times. Except for IMF Bz > 0 in summer, the DMTEC and DDR are larger when IMF By < 0 than those when IMF By > 0, especially in spring and winter. Key Points: The high‐latitude dawn‐dusk asymmetrical distribution of ionospheric plasma in the northern hemisphere was observed based on Global Navigation Satellite System TEC data Sources of the sunlit high‐density plasma at lower latitudes in the postnoon sector are responsible for the asymmetrical distribution The direction of IMF By and Kp index exert a significant effect on the dawn‐dusk asymmetry distribution